2006
DOI: 10.1302/0301-620x.88b10.18023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between external fixation and sliding hip screw in the management of trochanteric fracture of the femur in Nepal

Abstract: We conducted a randomised controlled trial to compare external fixation of trochanteric fractures of the femur with the more costly option of the sliding hip screw. Patients in both groups were matched for age (mean 67 years, 50 to 100) and gender. We excluded all pathological fractures, patients presenting at more than one week, fractures with subtrochanteric extension or reverse obliquity, multiple fractures or any bone and joint disease interfering with rehabilitation. The interval between injury and operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 11 publications
(8 reference statements)
3
30
1
Order By: Relevance
“…Cases of deep infection that required pin removal or repositioning have been reported [16,21,28] . The mean operative time in the present study was 32.22 ± 5.97 min, which was similar to that recorded by Kazakos et al [31] , Boghdady et al [5] and Vossinakis and Badras [50] The mean hospitalization time in our study was 4.2 ± 1.04 days, which is shorter than the average time recorded in published studies (6-8 days) [29,31,39,48,50] . The short average time between hospital admission and operative fixation in this study (2.63 ± 1.76 days).…”
Section: Discussionsupporting
confidence: 90%
“…Cases of deep infection that required pin removal or repositioning have been reported [16,21,28] . The mean operative time in the present study was 32.22 ± 5.97 min, which was similar to that recorded by Kazakos et al [31] , Boghdady et al [5] and Vossinakis and Badras [50] The mean hospitalization time in our study was 4.2 ± 1.04 days, which is shorter than the average time recorded in published studies (6-8 days) [29,31,39,48,50] . The short average time between hospital admission and operative fixation in this study (2.63 ± 1.76 days).…”
Section: Discussionsupporting
confidence: 90%
“…However in our previous randomised controlled trial we observed the external fixation is a less traumatic and cost effective option than the sliding hip screw in all cases of trochanteric fractures [11]. This study proves the external fixator is even more cost effective when indicated in elderly and high-risk patients with trochanteric fractures.…”
Section: Discussionmentioning
confidence: 50%
“…The need to reduce risks of open fracture fixation, permit early mobilization, and reduce hospital stay has prompted several authors to propose external fixation as an alternative treatment option for these elderly high-risk patients. 5,6,9,23 We retrospectively reviewed our experience of treating elderly patients with trochanteric fracture using external fixation. We found that functional outcome at one year in most of our patients was good to excellent; 86% returned to prefracture functional level, as was seen in various other studies.…”
Section: Discussionmentioning
confidence: 99%